Estimation of the drill pipes residual resource under the multiaxial stress state - Kopey, Bogdan; Artym, Volodymyr; Rachkevych, Iryna; Rachkevych, Ruslan (Technology audit and production reserves, 2018)
The object of research is the operation of drill pipes in a complex stress state. One of the most problematic places in this case is the process of fatigue, that is, the gradual accumulation of damage to the material of drill pipe under the influence of time-varying stresses. This leads to accidents, the elimination of which is accompanied by significant material and temporary losses. Based on the conducted critical analysis of scientific developments on this issue, it is noted that the use of kinetic diagrams of fatigue failure allows us to experimentally establish empirical parameters of fatigue of the material of drill pipe by laboratory research of small samples. And also to take into account the influence of the front shape of semi-elliptic and annular fatigue cracks on the residual resource. In addition, it is concluded that methods requiring additional attention, taking into account the combined effect on the kinetics of fatigue damage of normal and shear stresses. Therefore, in the course of the research, the positions of fracture mechanics were used. In particular, a feature of the proposed approach is the use in the formula for determining the stress intensity factor before the front of a semi-elliptical fatigue crack in the cross section of a tubular structure of equivalent stress, taking into account both the normal and shear component. This same stress, determined in accordance with the fourth theory of strength, is also used to calculate the critical crack depth. In order to assess the obtained results, a comparative calculation is made of the number of cycles of load change required to increase the depth of the specified crack from the initial to the critical value, not taking into account the value of the shear stress. It is established that the latter, with other unchanged conditions, can reduce the life of the drill pipe by up to two times. Thanks to the proposed method, it is possible to construct graphical dependencies of the fatigue life of drill pipes, taking into account the magnitude of the torque, other things being the same.